Cycles and Booms in Latin American Export Agriculture: The Case of the Livestock Economy in Southern Peru, 1855-1920 - Jacobsen, Nils (1983)
Historians dedicated to the study of Latin America in the 19th and 20th centuries agree that the increase in the demand for primary goods in European and North American countries undergoing industrialization gave rise to far-reaching changes in the productive structure, social and political of Latin American countries.